2001
DOI: 10.1002/etc.5620200328
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic risk assessment of cotton pyrethroids: III. A spatial analysis of the Mississippi, USA, cotton landscape

Abstract: Estimates of potential aquatic exposure concentrations arising from the use of pyrethroid insecticides on cotton produced using conventional procedures outlined by the U.S. Environmental Protection Agency's Office of Pesticide Programs Environmental Fate and Effects Division seem unrealistically high. Accordingly, the assumptions inherent in the pesticide exposure assessment modeling scenarios were examined using remote sensing of a significant Mississippi, USA, cotton-producing county. Image processing techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…The observed initial stratification of insecticides in the water column makes it likely that benthic organisms and those present in internal refugia, such as dense vegetations, are initially exposed to lower concentrations than organisms having niches and/or home ranges close to the water surface. In fact, spatio-temporal distribution of non-persistent insecticides forms a major issue in the discussion related to refinements of ecotoxicological risk assessments (Giesy et al, 1999;Hendley et al, 2001;Maund et al, 2001;Travis and Hendley, 2001).…”
Section: Application Methods and Pesticide Behaviourmentioning
confidence: 99%
“…The observed initial stratification of insecticides in the water column makes it likely that benthic organisms and those present in internal refugia, such as dense vegetations, are initially exposed to lower concentrations than organisms having niches and/or home ranges close to the water surface. In fact, spatio-temporal distribution of non-persistent insecticides forms a major issue in the discussion related to refinements of ecotoxicological risk assessments (Giesy et al, 1999;Hendley et al, 2001;Maund et al, 2001;Travis and Hendley, 2001).…”
Section: Application Methods and Pesticide Behaviourmentioning
confidence: 99%
“…These factors include natural wider buffer areas, natural wind breaks, the effect of trees and brush at filtering droplets, water surface in receiving waters being below land level and uncropped roadways, and the fact that multiple fields on the same farm are unlikely to be sprayed simultaneously. For example, a spatial analysis examining some of these factors was previously evaluated in the high cotton‐producing Yazoo County, Mississippi, USA (Hendley et al ). Results from that study show 92% of ponds in this region have no cotton grown within a 60‐m buffer area, and only 2% of the ponds have cotton present in all directions around the ponds and within a 120‐m buffer area (Hendley et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a spatial analysis examining some of these factors was previously evaluated in the high cotton‐producing Yazoo County, Mississippi, USA (Hendley et al ). Results from that study show 92% of ponds in this region have no cotton grown within a 60‐m buffer area, and only 2% of the ponds have cotton present in all directions around the ponds and within a 120‐m buffer area (Hendley et al ). Results also show that the composition of these buffer areas found between agriculture and water bodies were comprised of 78% to 87% dense trees, sparse trees, or brush, depending on the type of water body, thus reducing the expected loading of off‐target drift into nearby water bodies (Hendley et al ) due to filtering of the drift before entry.…”
Section: Discussionmentioning
confidence: 99%
“…The approach adopted in this study did not attempt to distinguish explicitly between time and space when assessing risk, although this is possible. Some recent risk assessments have attempted to identify areas of pesticide vulnerability by developing geographic21 information system (GIS) maps based upon pesticides sales volumes, weather patterns, soil characteristics and landscape‐level parameters 22–24. For example, Hendley et al 22 found through remote sensing and GIS that only 2% of 597 ponds in a cotton‐producing county of Mississippi were surrounded by cotton fields and thus most vulnerable to impact from cotton pyrethroids.…”
Section: Discussionmentioning
confidence: 99%